(3faY GdWjH ef ZUf GdCfOdS GdQWjHs - (3GdebQj , CHh GdYHGS CMeO Hf eMeO Hf CMeO Hf jMji Hf YHO GdQMef GdebQj,J (B1041 (3g` s
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ GdebQi CMeO ef YQa ef Mdi GdCeUGQ s
(3BNQgG (B:s
(3Udi Ydjc Gddg SHMGfg eGgRJ GdQjM bOhO GdZUhf aHGdeNJGQ CQLh Yah QHi jQTOfi Edi MSf GdNJGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B237 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B78 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B157s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(6273) s
Keywords: (3GdCOHs